Calibrating the absolute amplitude scale for air showers measured at LOFAR - Nelles, Anna; Horandel, J. R.; Karskens, T.; Krause, Maria; Buitink, S.; Corstanje, A.; Enriquez, J. E.; Erdmann, Martin; Falcke, H.; Haungs, A.; Hiller, R.; Huege, Tim; et al. (Journal of Instrumentation, 2015)
Air showers induced by cosmic rays create nanosecond pulses detectable at radio frequencies. These pulses have been measured successfully in the past few years at the LOw-Frequency ARray (LOFAR) and are used to study the properties of cosmic rays. For a complete understanding of this phenomenon and the underlying physical processes, an absolute calibration of the detecting antenna system is needed. We present three approaches that were used to check and improve the antenna model of LOFAR and to provide an absolute calibration of the whole system for air shower measurements. Two methods are based on calibrated reference sources and one on a calibration approach using the diffuse radio emission of the Galaxy, optimized for short data-sets. An accuracy of 19% in amplitude is reached. The absolute calibration is also compared to predictions from air shower simulations. These results are used to set an absolute energy scale for air shower measurements and can be used as a basis for an absolute scale for the measurement of astronomical transients with LOFAR.
Keywords: Antennas; Large detector systems for particle and astroparticle physics; Spectral responses